2014
DOI: 10.7554/elife.03941
|View full text |Cite
|
Sign up to set email alerts
|

The glucuronyltransferase B4GAT1 is required for initiation of LARGE-mediated α-dystroglycan functional glycosylation

Abstract: Dystroglycan is a cell membrane receptor that organizes the basement membrane by binding ligands in the extracellular matrix. Proper glycosylation of the α-dystroglycan (α-DG) subunit is essential for these activities, and lack thereof results in neuromuscular disease. Currently, neither the glycan synthesis pathway nor the roles of many known or putative glycosyltransferases that are essential for this process are well understood. Here we show that FKRP, FKTN, TMEM5 and B4GAT1 (formerly known as B3GNT1) local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 61 publications
1
85
0
1
Order By: Relevance
“…SPPL3 may also impact O-mannosylation as we identified the recently characterized Sgk196 (27) as novel SPPL3 substrate. Likewise the SPPL3 substrate ␤3GnT1 (9) was recently implicated in this pathway (29,30). However, most prominent is the link of the newly identified SPPL3 substrates to glycosaminoglycan biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPPL3 may also impact O-mannosylation as we identified the recently characterized Sgk196 (27) as novel SPPL3 substrate. Likewise the SPPL3 substrate ␤3GnT1 (9) was recently implicated in this pathway (29,30). However, most prominent is the link of the newly identified SPPL3 substrates to glycosaminoglycan biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides were separated by reverse phase chromatography using in-house made 30 Table S1 and S4) for both data sets are attached as supplementary files. The mass spectrometry proteomics raw data including MaxQuant outputfiles have been deposited to at the ProteomeXchange Consortium (http://proteomecentral.…”
Section: Methodsmentioning
confidence: 99%
“…The b-subunit is linked to the actin cytoskeleton, and the O-linked glycans on the a-subunit are critical for its binding capacity to extracellular matrix proteins such as laminin and agrin (Ervasti & Campbell, 1993;Michele et al, 2002). Mutations in dystroglycan itself result in the primary dystroglycanopathies (Henry & Campbell, 1998;Cote et al, 1999;Hara et al, 2011;Willer et al, 2014;Riemersma et al, 2015;Kanagawa et al, 2016). Secondary dystroglycanopathies are caused by interruption of a-dystroglycan-ligand interactions due to mutations in a growing list of genes [currently eighteen (Bonnemann et al, 2014)] encoding glycosyltransferases and accessory proteins responsible for a-dystroglycan's extensive posttranslational modifications (Muntoni et al, 2011;Inamori et al, 2012;Yoshida-Moriguchi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This GlcNAc residue is then extended with a terminal ␤3GalNAc, catalyzed by ␤-1,3-N-acetylgalactosaminyltransferase 2 (53). The presence of this phosphorylated O-mannose trisaccharide is required for the addition of laminin-binding glycans catalyzed by LARGE, consisting of a repeating xylose and glucuronic acid oligosaccharide (53)(54)(55)(56)(57)(58). Our previous study demonstrated that the molecular mass and reactivity of O-mannose-linked glycan epitopes on RPTP/phosphacan were unchanged in mouse models of LARGE myodystrophy mutant mice (14).…”
Section: Discussionmentioning
confidence: 99%